2014
DOI: 10.1093/jxb/eru446
|View full text |Cite
|
Sign up to set email alerts
|

Polyols in grape berry: transport and metabolic adjustments as a physiological strategy for water-deficit stress tolerance in grapevine

Abstract: Polyols are important metabolites that often function as carbon and energy sources and/or osmoprotective solutes in some plants. In grapevine, and in the grape berry in particular, the molecular aspects of polyol transport and metabolism and their physiological relevance are virtually unknown to date. Here, the biochemical function of a grapevine fruit mesocarp polyol transporter (VvPLT1) was characterized after its heterologous expression in yeast. This H(+)-dependent plasma membrane carrier transports mannit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 87 publications
4
61
0
1
Order By: Relevance
“…An important group of primary metabolites showing strong positive correlation included the amino acids beta‐alanine, glycine, leucine, proline, serine, threonine and valine, and the polyamine putrescine; the sugar alcohols erythritol, galactitol, and threitol; and the sugars galactinol, galactose, melibiose, turanose, and trehalose. This group consists, to a considerable extent, of metabolites associated with plant response to solar irradiance, heat, and other abiotic stresses (Alcazar et al, ; Conde et al, ; Garg et al, ; Obata & Fernie, ; Pillet et al, ; Reshef et al, ). Another group showing strong positive correlations included ribulose, glycolate, glycerate, and pyruvate, associated with photorespiration; iso‐ascorbate and its metabolite threonate; and indole‐3‐acetate and its precursor tryptophan.…”
Section: Resultsmentioning
confidence: 99%
“…An important group of primary metabolites showing strong positive correlation included the amino acids beta‐alanine, glycine, leucine, proline, serine, threonine and valine, and the polyamine putrescine; the sugar alcohols erythritol, galactitol, and threitol; and the sugars galactinol, galactose, melibiose, turanose, and trehalose. This group consists, to a considerable extent, of metabolites associated with plant response to solar irradiance, heat, and other abiotic stresses (Alcazar et al, ; Conde et al, ; Garg et al, ; Obata & Fernie, ; Pillet et al, ; Reshef et al, ). Another group showing strong positive correlations included ribulose, glycolate, glycerate, and pyruvate, associated with photorespiration; iso‐ascorbate and its metabolite threonate; and indole‐3‐acetate and its precursor tryptophan.…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid is a polyphenol with strong antioxidant and anti-free radical effects (Zhang et al, 2011). A large amount of hydroxylamine and putrescine were accumulated in wild soybean under neutral salt stress, which can reduce the damage caused by salt stress by eliminating excess ROS (Conde et al, 2015). Additionally, hydroxylamine is an intermediate product of plants using nitrate ions, and its accumulation indicates that wild soybean was able to use more NO3-, which indicates that the nitrogen metabolism of wild soybean increased.…”
Section: Discussionmentioning
confidence: 99%
“…Both sorbitol and mannitol limited size reduction of berry cells under drought (Conde et al, 2015). The authors suggested that grapevine cultivars which accumulate polyols as a tolerance mechanism to drought stress might have adaptive advantages under unfavourable growing conditions as they would require less water along the season to sustain yield and berry quality (Conde et al, 2015). It was also suggested that synthesis, transport and accumulation of sugar alcohols may work as bioindicators of plant health and acclimation and can be used as potential biomarkers in crop breeding (Merchant and Richter, 2011;Conde et al, 2015).…”
mentioning
confidence: 97%
“…polyols) in the adaptation to drought in grapevine. The impact of polyols on grape berry composition and plant response to water deficit was described for the variety Tempranillo grown in greenhouse and field conditions (Conde et al, 2015). Both sorbitol and mannitol limited size reduction of berry cells under drought (Conde et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation